(untitled) (Gestão & Regionalidade, 2016)
This paper identifies difficulties and capabilities of the farmers studied to build the attributes called "entrepreneurial skills". The research is based on rural entrepreneurship with emphasis on entrepreneurial skills. This qualitative research which content analysis aimed to: identify the main difficulties and capabilities of farmers to assimilate the new entrepreneurial skills necessary for the viability of agro industries and examine the compatibility of the actions adopted by companies to support family farming with the reality of the farmers who engaged in entrepreneurship through the agro industrialization of production. We interviewed nine farmers from three leading associative agro industries from rural and backcountry regions of the state of Pernambuco, Brazil, and twelve technicians from nine institutions that support family farming. In the factories that presented negative results, their managers had major shortcomings of entrepreneurial skills. Lastly, the paper contributes with suggestions for farmer entrepreneurs to overcome adversity, as well as to assist field technicians (extensionists or not) to transpose their shortcomings.